Antidote - Van Landingham, Corey, 1986- (Book collections on Project MUSE., 2013)
In Corey Van Landingham's Antidote, love equates with disease, valediction is a contact sport, the moon is a lunatic, and someone is always watching. Here the uncanny co-exists with the personal, so that each poem undergoes making and unmaking, is birthed and bound in an acute strangeness. Wild and surreal, driven by loss, Antidote invites both the beautiful and the brutal into its arms, allowing for shocking declarations about love: that it is like hibernation, a car crash, or a parasite. It soon becomes clear that there is no antidote for grief or heartbreak, that love can, at times, feel like violence, and that one may never get better at saying goodbye.